Communication : getting the message across - Hemmer, Nicole (Miller Center studies on the presidency., 2019)
In an increasingly polarized political environment, the first year of the new president's term will be especially challenging. With a fresh mandate, however, the first year also offers opportunities that may never come again. The First Year Project is a fascinating initiative by the Miller Center of the University of Virginia that brings together top scholars on the American presidency and experienced officials to explore the first twelve months of past administrations, and draw practical lessons from that history, as we inaugurate a new president in January 2017.